Central Cognitive Processing Speed Is an Early Marker of Huntington's Disease Onset. Issue 1 (28th December 2020) - Corey‐Bloom, Jody; Williams, McKenna E.; Beltran‐Najera, Ilex; Mustafa, Andrea I.; Snell, Chase M.; Castleton, Jordan; Smith, Haileigh; Wright, Brenton; Gilbert, Paul E.
ABSTRACT: Background: Several studies have suggested that cognitive processing speed may be useful for assessing early cognitive change in premanifest Huntington's disease (HD); however, current measures lack the ability to control for the effects of motor dysfunction commonly found in HD. The Computerized Test of Information Processing (CTiP) is a rapidly administered computerized tool that allows for the examination of central cognitive processing speed by using motor‐corrected scores to account for motor dysfunction. Objective: To examine central cognitive processing speed as an early marker of HD onset using the CTiP. Methods: The CTiP and other measures were administered to 102 HD gene carriers and 55 healthy adults (HA). Gene carriers included presymptomatic HD (pre‐HD; n = 33), prodromal HD (pro‐HD; ie, individuals close to disease onset; n = 23), and mild–moderate HD (HD; n = 46). Results: The HD group performed significantly slower than all other groups (HA, pre‐HD, and pro‐HD) on most subtests ( P s < .05). Moreover, the pro‐HD group performed significantly slower than the HA group on both motor‐corrected subtests ( P s < 0.05). Effect sizes associated with significant group differences between the pro‐HD and HA groups on motor‐corrected CTiP subtests ( d = 0.73 and 0.84) were similar to effect sizes associated with group differences on the Symbol Digit Modalities Test ( d = .82) and other traditional cognitive assessments (Montreal Cognitive Assessment, d = .75; Mini‐Mental State Examination, d = .84). Conclusions: The CTiP may be a useful marker of deficits in central cognitive processing speed in individuals close to manifest onset of HD.